CHALLENGES FOR EDUCATION CAREER IN THE LITHUANIAN SCHOOLS OF GENERAL EDUCATION: EXPERIENCE OF CAREER SPECIALISTS - Merfeldaite, Odeta; Railiene, Asta; Indrasiene, Valdone; Jegeleviciene, Violeta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article presents the challenges for the career specialist in provision of career education services in the school of general education. Based on the results of the qualitative research, employing the methods of the focus group discussion, the following conclusions should be made:  The main problems faced by the career specialists providing career services in general education schools are the following: heavy workload, lack of cooperation among the career specialists; the schools lack informational and methodological means which would correspond to special needs of the students, of age groups; for improvement of efficiency of the activity of career specialists an information data base containing all available informational, counselling, methodological material designated for the career specialist is required; psychological tests on the subjects of self-awareness and career which could be applied by career specialists on their own, without having psychological education; lack of attractive, corresponding to the needs of the modern labour market and of the students, video material designated for career education; training based on sharing of experience is necessary for qualification improvement